Can we cure patients with abdominal Desmoplastic Small Round Cell Tumor? Results of a retrospective multicentric study on 100 patients. (June 2019) - Honoré, C.; Delhorme, J.B.; Nassif, E.; Faron, M.; Ferron, G.; Bompas, E.; Glehen, O.; Italiano, A.; Bertucci, F.; Orbach, D.; Pocard, M.; Quenet, F.; et al.
Abstract: Background: Despite being associated with a very poor prognosis, long-term survivors across all series of Desmoplastic Small Round Cell Tumor (DSRCT) have been reported. Aim of the study: To analyze patients 'characteristics associated with a prolonged survival after DSRCT diagnosis. Methods: All consecutive patients treated for DSRCT in nine French expert centers between 1991 and 2018 were retrospectively analyzed. Patients with a follow-up of less than 2 years were excluded and cure defined as being disease-free at least 5 years. Results: 100 pts were identified (median age 25 years, 89% male). 27 had distant metastases at diagnosis and 80 pts underwent upfront chemotherapy (CT). 71 pts were operated, 20 pts without prior CT). Surgery was macroscopically complete (CC0/1) in 50 pts. Hyperthermic intraperitoneal Chemotherapy (HIPEC) was administered during surgery in 15 pts 54 pts had postoperative CT and 26 pts had postoperative whole abdomino-pelvic RT (WAP-RT). After a median follow-up of 103 months (range 23–311), the median overall survival (OS) was 25 months. The 1- year, 3-year and 5-year OS rates were 90%, 35% and 4% respectively. 5 patients were considered cured after a median disease-free interval of 100 months (range 22–139). Predictive factors of cure were female sex (HR = 0.49, p = 0.014), median PCI<12 (HR = 0.32, p = 0.0004), MD Anderson stage I (HR = 0.25, p < 0.0001), CC0/1 (HR = 0.34, p < 0.0001), and WAP-RT (HR = 0.36, p = 0.00013). HIPEC did not statistically improve survival. Conclusion: Cure in DSRCT is possible in 5% of patients and is best achieved combining systemic chemotherapy, complete cytoreductive surgery and WAP-RT. Despite aggressive treatment, recurrence is common and targeted therapies are urgently needed.